Distinct effects of dietary flax compared to fish oil, soy protein compared to casein, and sex on the renal oxylipin profile in models of polycystic kidney disease. (August 2017) - Devassy, Jessay G.; Yamaguchi, Tamio; Monirujjaman, Md; Gabbs, Melissa; Ravandi, Amir; Zhou, Jing; Aukema, Harold M.
Abstract: Oxylipins are bioactive lipids derived from polyunsaturated fatty acids (PUFA) that are important regulators of kidney function and health. Targeted lipidomic analyses of renal oxylipins from four studies of rodent models of renal disease were performed to investigate the differential effects of dietary flax compared to fish oil, soy protein compared to casein, and sex. Across all studies, dietary fish oil was more effective than flax oil in reducing n-6 PUFA derived oxylipins and elevating eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) derived oxylipins, whereas dietary flax oil resulted in higher α-linolenic acid (ALA) oxylipins. Dietary soy protein compared to casein resulted in higher linoleic acid (LA) derived oxylipins. Kidneys from females had higher levels of arachidonic acid (AA) oxylipins, but similar or lower levels of oxylipins from other PUFA. Modulation of the oxylipin profile by diet and sex may help elucidate their effects on renal physiology and health. Highlights: Targeted lipidomic analyses of renal oxylipins from four studies in rodent models. Flax oil resulted in higher ALA oxylipins. Fish oil was more effective than flax oil in reducing n-6 PUFA oxylipins and elevating EPA and DHA oxylipins. Soy protein resulted in higher LA oxylipins. Females had higher renal AA oxylipins, but similar or lower levels of oxylipins from other PUFA.